Lung cancer with supraclavicular myxoinflammatory fibroblastic sarcoma is easily misdiagnosed as lymph node metastasis: a case report - Yang, Qian; Chen, Jie; Feng, Xiao; Zeng, Shue (Frontiers in Oncology, 2025)
Myxoinflammatory fibroblastic sarcoma (MIFS) is an infiltrative, locally invasive fibroblastic tumor. A 68-year-old male patient was admitted to the hospital because of a physical examination that revealed a space-occupying lung. Positron emission tomography-CT (PET-CT) showed right upper lung cancer with multiple tiny nodules in both lungs (suspected metastatic foci), and the diagnosis of adenocarcinoma of the right lung was confirmed by aspiration biopsy. In the same period, thyroid nodules were detected by ultrasound and puncture, and papillary thyroid cancer was confirmed by pathology. After multidisciplinary consultation, a systemic treatment plan was drawn up, and changes in the lung nodules were observed. The patient received two cycles of chemotherapy and one cycle of targeted therapy, and the follow-up examination showed shrinkage of the upper lobe of the right lung but stabilization of the intrapulmonary nodule. Still, a mass was visible under the skin on the right neck. Given the abnormal ultrasound of lymph nodes in the V region of the neck and the puncture suggestive of a spindle cell soft tissue tumor, the team of specialists performed radical surgery after a comprehensive evaluation, including resection of the upper lobe of the right lung, systematic lymph node dissection, and enlarged resection of the neck mass. Postoperative pathology finally confirmed that the neck lesion was MIFS. This case suggests that the combination of lung cancer and neck mass should be alerted to the possibility of non-metastatic lesions, especially with supraclavicular lymph node metastasis, which emphasizes the key role of multidisciplinary collaboration and precise pathological diagnosis in the differentiation of complex tumors.